Pendekatan Permintaan Dalam Pengembangan Sektor Air Bersih di Propinsi Jawa Timur - Nugroho, Iwan (Center for Research and Community Services ITB, 2001)
This article is a research study aimed to implement demand approach on wafer supply development in East Java province. Data collecting is conducted through field and institutional survey to obtain actual and behavioral variables. System analysis is operated to project the water supply development dynamically. The research showed that pricing policy and PDAM’s management improvement succeeded to create a significant incentive for the water supply development. The policies of price growth 2 percent and gradual decreasing of unaccounted for water into 30 percent have produced a decrease in investment requirement. Water demand, and production capacity of 86, 78 and 59 percent lower than existing policy. The policy also performed an increase in Kali Sarabaya ‘s water quality.